Budikdamber dan Sayuran Akuaponik sebagai Upaya Ketahanan Pangan Masyarakat Kelurahan Sungai Miai Banjarmasin Utara : Indonesia - Fauzana, Noor Arida; Ansyari, Pahmi; Slamat, Slamat; El Redha, El Redha (UII, 2026)
The community of RW 02 Sungai Miai Village, North Banjarmasin, is an active community in implementing various programs to anticipate climate change, as evidenced by the success of achieving the Climate Village category “Lestari”. The surrounding community has used vacant land to plant various kinds of vegetables and cultivate fish for consumption in round ponds. The harvest returns to the community, one of which is to provide additional nutrition for toddlers during Posyandu activities held every month. Along with the development of development, land for fish cultivation or gardening is increasingly limited, while the need for vegetable and animal proteins continues to grow. This is the reason aquaponics was chosen because this method was developed to maximize limited land use, to produce fish and plant products at once, especially in urban areas or densely populated settlements such as in RW02 Sungai Miai Village. The purpose of this activity is to provide education and training about budikdamber and aquaponic system vegetables by utilizing limited land for the fulfillment of family nutrition. The dissemination of activities was delivered by methods of theoretical explanation, demonstration, training and intensive assistance during the activity. The results obtained showed that the partner group was very enthusiastic in receiving the knowledge and skills conveyed, there was an increase in knowledge from a score of 1.59 to 4.35 compared to before the counseling or an increase of 173.58% and an increase in skills from a score of 1.36 to 3.35 or an increase of 146.32%. These results indicate that counseling and training materials have been delivered effectively and successfully absorbed by the community. Overall, the training was very successful in improving participants' practical skills in implementing and managing aquaculture and aquaponics systems.